Africa's Pulse, No. 18, October 2018 : An Analysis of Issues Shaping Africa’s Economic Future - World Bank Group (Washington, DC: World Bank, 2018)
Africa's Pulse is a biannual publication containing an analysis of the near-term macroeconomic outlook for the region. Each issue also includes a section focusing upon a topic that represents a particular development challenge for the continent. It is produced by the Office of the Chief Economist for the Africa Region of the World Bank.